P03.20 A murine, myc-driven lymphoma model expressing human CD22 enables testing of targeted therapies and their effects on tumor immune microenvironment. (1st October 2020) - Gsottberger, F; Brandl, C; Petkovic, S; Nitschke, L; Mackensen, A; Müller, F
Abstract : Background: The tumor microenvironment (TME) is composed of various cell types which closely interact via cell cell contacts and cytokines leading to tumor promotion, immune cell inhibition and drug resistance. TME is increasingly recognized for its role in cancer immunotherapies. In B-cell malignancies, myeloid cells play a central role in supporting tumor growth and immune suppression (Roussel et al ., 2017, Cancer Immunol Immunother). Despite the importance of a syngeneic TME, preclinical studies with novel drugs have mainly been performed in models lacking a functional immune system. Therefore, we developed an immune competent murine lymphoma model transgenic to human CD22 to study effects of targeted therapies on TME. Materials and Methods: A chimeric CD22 consisting of human extracellular and murine intracellular CD22 (h/mCD22) was introduced in BL6 mice (BL6 h/mCD22 ). Crossbreeding with BL6 λ-myc lead to spontaneous development of murine lymphoma that were serially transplanted. Tumor infiltration and TME was characterized by flow cytometry. Mice were treated with Moxetumomab pasudotox, a CD22 targeted immunotoxin and Doxorubicin. Results: Spontaneously developed tumors in lymphoid organs from BL6 h/mCD22 x λ-myc consist of a monomorphic population of h/mCD22 + murine B cells. Three primary lymphoma subclones were isolated from distinct mice and serially transplanted in syngeneic mice. Stable tumor growth was established after subcutaneous (sc) and intravenous (iv) injection. However, TME of sc tumors was infiltrated by less than 1% immune cells, while myc-driven lymphoma in humans usually show substantial immune infiltration. In contrast to sc tumors, systemically growing lymphoma in murine bone marrow (BM) are infiltrated by 30% myeloid cells and 1% T-cells and in murine spleen by 10% and 30%, respectively. Myeloid cells found in these tumors were shown to suppress T cell proliferation in vitro . To test functionality of the h/mCD22 transgene, lymphoma-bearing mice were treated with Moxetumomab, which reduced BM lymphoma infiltration by 20 to 100-fold and infiltration in spleen by 5 to 20-fold in the three lymphoma models. Effects of treatment on TME were analyzed after treatment with Doxorubicin which is known to activate myeloid cells in vivo . Compared to untreated controls, Doxorubicin increased CD11b + cells in spleen by 1.5-fold. Among these cells, Ly6G + granulocytic cells increased most substantially. Conclusions: We established primary, myc-driven h/mCD22 + B-cell lymphoma which stably engraft in syngeneic mice with a TME mimicking myc-driven lymphoma in men. The model responds well to CD22-targeted therapy and Doxorubicin induces expected immunologic changes. Therefore, our unique model provides a platform to test CD22-targeting treatment strategies in an immune competent background. Disclosure Information: F. Gsottberger: None. C. Brandl: None. S. Petkovic: None. L. Nitschke: None. A. Mackensen: None. F. Müller: None.